Yona of the dawn. 4 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2017)
"While on a quest to find the Four Legendary Dragon Warriors, Yona and her friends meet Gija, the White Dragon. Gija uses his power to detect the other Dragons, but locating the Blue Dragon proves to be more difficult than expected, and the group runs into a string of disasters!" -- page 4 of cover.